Visceral leishmaniasis in the island of Margarita, Venezuela: a neglected parasitic infection in the Caribbean. (July 2021) - García Oronoz, Gerardine; Pedraza-Arévalo, Laura C.; Henao-Martínez, Andrés F.; Franco-Paredes, Carlos; Suarez, José A.
Visceral leishmaniasis carries a significant burden of disease in the Americas with up to 7000 cases reported annually. There are several reports of autochthonous visceral leishmaniasis cases in the Caribbean, including the Dominican Republic, Guadalupe, Martinique, and Trinidad and Tobago. However, we lack recent clinical description and epidemiologic data of visceral leishmaniasis in other islands in the Caribbean. Herein, we describe an autochthonous case of visceral leishmaniasis in the Caribbean Island of Margarita in Venezuela. This index case of visceral leishmaniasis highlights the need for further regional surveillance efforts to identify animal reservoirs and to monitor the occurrence of further clinical cases. Additionally, there is an urgent need for implementing vector control strategies.